(untitled) (Journal of Surgical Sciences, 2019)
Objective: To determine the complications of the patients undergoing total thyroidectomy. Method: A prospective study was held at Department of Endocrine Surgery in BSMMU from January 2006 to December 2006 Method: Fifty patients with multinodular goiter and carcinoma thyroid of both sexes were selected from admitted patient of endocrine surgery department. All patients were evaluated preoperatively and total thyroidectomy was done and post operative was followed up. Out of 50 patients 35 patients were female and 15 patients male, male - female ratio 1 :2.3. 40 patients were carcinoma thyroid, 10 patients were multinodular goiter. The overall incidence of postoperative complication in this series was 4. out of 50 patients 1 patient developed haematoma. 1 patient developed wound infection and 1 patient developed transient tetany on 2nd postoperative day which was improved later on. 1 patient developed a thyroid nodule 6th month after total thyroidectomy for carcinoma thyroid. In long term from total thyroidectomy 40 patients were followed up, 10 patients did not attend an subsequent follow up. Out of 40 patients 36 patients were out of complication. Conclusion: The results are comparable with the current published data and demonstrate that total thyroidectomy can performed with minimum complication rate. Journal of Surgical Sciences (2013) Vol. 17 (1) : 25-29